An IoT-Based Remote Monitoring Information System for Hydroponic Greenhouses in the Context of Smart Farming - Duarte, Débora; Ströele, Victor; Soares, Fabrício; Castro, Ronney; Campos, Luciana Conceição Dias; Braga, Regina Maciel (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2026)
Research Context: Climate change and population growth pose challenges to food security, requiring innovations in agriculture. Greenhouses emerge as an alternative for controlled cultivation, and hydroponics optimizes water and space usage while allowing precise nutrient management. Scientific and/or Practical Problem: However, hydroponic systems require investment, specialized technical knowledge, and ongoing monitoring. They are vulnerable to energy failures, nutrient imbalances, and environmental variations, leading to rapid production losses, particularly for small producers with limited resources. Proposed Solution and/or Analysis: This work proposes a low-cost IoT-based remote monitoring information system for hydroponic greenhouses. The system integrates sensors connected to Arduino, transmitting real-time data to the ThingSpeak cloud platform. The application enables the visualization of critical variables, provides automatic alerts in the event of deviations, and facilitates remote calibration of pH and electrical conductivity sensors. Related IS Theory: The solution aligns with the principles of Smart Farming and socio-technical IS theory. By supporting decision-making with real-time data and integrating technology with organizational and social dimensions, it reinforces the role of IS in promoting sustainability and efficiency in agriculture. Research Method: An experimental prototype was deployed in a real hydroponic greenhouse, monitoring two reservoirs and cultivation benches. Data from sensors were collected, transmitted via Wi-Fi, stored in ThingSpeak, and consumed by the mobile system for validation under production conditions. Summary of Results: The system successfully monitored variables such as temperature, pH, conductivity, solution volume, turbidity, and flow. Alerts enabled timely corrective actions, including adjustments to nutrient and management of excessive conductivity, while ThingSpeak dashboards supported historical analysis. Contributions and Impact to IS area: The research demonstrates a low-cost, modular IoT infrastructure integrated with a mobile interface for agriculture. It contributes to IS by bridging technology, organization, and social impact, offering accessible tools that support decision-making, resource efficiency, and preventive management in food production.